EU and Ukraine Cooperation for Sustainable Environment: Historical and Legal Aspects - Kazak, Rinata (European Journal of Sustainable Development, 2014)
The article discusses various aspects of the legal maintaining of environmental sustainability. Ukraine as one of the largest countries in Europe with more, than 40 million population causes a huge effect on the environmental situation in Europe. Through the historical research the author highlights the 60 – 70th of the XX century as an active period of international cooperation between the EU and Ukraine. The evidence of this activity was the complex Soviet Ukraine Act on nature protection 1960 and Government Committee for Nature Protection established in 1968 with competence of cooperation with European Community environmental authorities. Within a few years, many countries filled the gap and made a great step towards sustainable development, declared by the Stockholm Conference (1972) and First Environmental Action Programme in Europe (1973). The author draws the parallel between the Ukrainian and EU legal bases. Modern Ukraine tends to the association with the EU, so this research of a big importance has theoretical and practical value for Ukraine. Keywords: EU and Ukraine cooperation, environmental sustainability, historical and legal aspects.